Vanadium-Catalyzed Regioselective Oxidative Coupling of 2-Hydroxycarbazoles - Liu, Lei (Org Lett, 2015)
[Image: see text] The first regioselective oxidative coupling of 2-hydroxycarbazoles is described. With a vanadium catalyst and oxygen as the terminal oxidant, dimers with an ortho–ortho′ coupling pattern were obtained with high selectivity. Further oxidation led to ortho′–ortho′ coupling to generate a tetramer, which provided insight that the atropisomerization barriers of the unsymmetrical biaryl bonds are much lower than expected.